Commentary on Maternal and Perinatal Mortality in Nigeria: Establishment of Obstetric Waiting Units and Targeting Uterine Rupture - Eli, S. F.; Abam, D. S.; Kalio, D. G. B.; Ikimalo, J. (Highlights on Medicine and Medical Research Vol. 10, 2021)
Transportation is a challenge to women especially in rural settings where there are little or no means of transportation or access to health facilities where basic obstetric care could be given; hence, patients with ruptured uterus may end up losing both their babies and their lives. Government, non-governmental organizations, religious groups, community heads, multinationals, international organizations must support the crusade in averting maternal and perinatal mortality by reducing risk factors of ruptured uterus.